The impact of privacy design in university student housing on mental health and academic performance: A systematic review (2000-2024)" - Tianyu, LI; Omar, Mohd Hisham bin (Edelweiss Applied Science and Technology, 2025)
The rapid expansion of higher education has intensified focus on student housing design and its impact on academic success and well-being. Despite substantial research examining various aspects of student housing, a critical gap exists in understanding how privacy design features specifically influence student outcomes. This study aims to systematically analyze student housing research from 2000 to 2024, evaluate interconnections between design aspects and student outcomes, and develop an evidence-based framework for understanding the relationship between housing design and student well-being. Following PRISMA guidelines, this systematic review analyzed 143 documents across 94 sources from Scopus, employing a Structural Topic Model (STM) approach to uncover latent thematic structures. The analysis revealed five distinct research themes: social implications (37%), campus development (22%), student satisfaction (18%), training programs (15%), and facility design (9%). Temporal analysis demonstrated a significant shift from technical considerations toward social and experiential aspects, with 55% of publications occurring between 2020-2024. Correlation analysis revealed predominantly negative correlations between research streams, particularly between social implications and campus development (-0.41), indicating limited interdisciplinary integration. The findings highlight the need for more integrated approaches to student housing design that balance privacy considerations with community development. The study's correlation patterns and topic coherence analysis suggest opportunities for bridging distinct research streams through interdisciplinary frameworks. Future research should focus on developing integrated methodologies, conducting longitudinal studies on privacy design impacts, and investigating the role of emerging technologies in student housing design.